Islamic Connections: Muslim Societies in South and Southeast Asia - Feener, R; Sevea, Teren (Institute of Southeast Asian Studies, 2009)
Well over half of the world's Muslim population lives in Asia. Over the centuries a rich constellation of Muslim cultures developed there and the region is currently home to some of the most dynamic and important developments in contemporary Islam. Despite this, the internal dynamics of Muslim societies in Asia do not often receive commensurate attention in international Islamic Studies scholarship. This volume brings together the work of an interdisciplinary group of scholars discussing various aspects of the complex relationships between the Muslim communities of South and Southeast Asia. With their respective contributions covering points and patterns of interaction from the medieval to the contemporary periods, they attempt to map new trajectories for understanding the ways in which these two crucial areas have developed in relation to each other, as well as in the broader contexts of both world history and the current age of globalization.